Can cardiovascular MRI be used to more definitively characterize cardiac masses initially identified using echocardiography?. Issue 5 (16th May 2018) - Rathi, Vikas K.; Czajka, Anna T.; Thompson, Diane V.; Doyle, Mark; Tewatia, Tarun; Yamrozik, June; Williams, Ronald B.; Biederman, Robert W. W.
Abstract : In diagnosing cardiac and paracardiac masses, cardiac MRI (CMR) has gained acceptance as the gold standard. CMR has been observed to be superior to echocardiography in characterizing soft‐tissue structures and, specifically, in classifying cardiac masses. The aim of our study was to evaluate the association between mortality and cardiac or paracardiac masses initially identified by echocardiography (ECHO) and confirmed by CMR. Between January 2002 and August 2007, a total of 158 patients underwent both ECHO and CMR for the evaluation of cardiac masses that were equivocal or undefined by ECHO. The primary study endpoints were 5‐year all‐cause mortality and 5‐year cardiac mortality. Causes of death as of April 1, 2015 were obtained from medical records or the National Death Index. Patients were analyzed according to mass type determined by CMR using the Kruskal–Wallis test, Kaplan–Meier curves, and the log‐rank test. Over a mean duration of follow‐up of 10.4 ± 2.9 years (range: 0.01–12 years) post‐CMR, the overall all‐cause mortality rate was 25.9% (41/158). Median age at death was 76 years and there were 21 females (51.2%). Mortality rates in the different classifications of cardiac masses by CMR were as follows: 20% (1/5) in patients with a Nondiagnostic CMR; 20% (1/5) in Other Diagnoses; 17.9% (7/39) in No Masses (includes Normal Anatomical Variants); 16.7% (3/18) in Benign Masses; 23.8% (15/63) in Fat; 50% (5/10) in Thrombus; and 61.5% (8/13) in Malignant Mass. The mean survival time in patients with No Mass (n = 39) was not significantly longer than patients with any type of cardiac mass (n = 114) ( P  = .16). No significant difference was found in age at death between patients when grouped by CMR classification ( P  = .40). However, among CMR‐confirmed masses, there were some significant differences by mass classification type ( P  = .006). During the follow‐up period, 26% (41/158) of patients died and 22% (9/41) of the deaths were cardiovascular related; there was no significant difference in mean survival times with respect to cause of mortality ( P  = .23). In patients with cardiac masses, dually confirmed by ECHO and CMR, significant differences in survival time were observed based upon CMR classified type of mass while CMR was instrumental in obviating invasive biopsy.